The long noncoding RNA lnc-EGFR stimulates T-regulatory cells differentiation thus promoting hepatocellular carcinoma immune evasion - Runqiu Jiang (Nature Portfolio, 2017)
The role of long noncoding RNAs in regulating T-cell differentiation within the tumour microenvironment is unclear. Here the authors identify a lncRNA that, through direct interactions with EGFR, promotes T-regulatory cell differentiation within the microenvironment of hepatocellular carcinoma, thus promoting tumour growth via immune suppression.